Childrens Self Acceptance Raised by Single Mother: Analysis Study in Moslem Family - Nurwahidin, Nurwahidin; Mahruza, Nurul Qina; Asyhar, Thobib Al (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2019)
This research aims to analyze the self acceptance of children raised by single mother, due to death divorce or marriage problems between the parents. The methods of this research is a qualitative with case study approach, data is collected by depth interview toward 15 children as the informants which chosen through purposive sampling technique. Those 15 informants live in Aceh, NTB, Bandung, Depok, Bogor, Jakarta, Bekasi, and Tanggerang. Overall view of research result shows that childrens self acceptance raised by single mother influenced by factors of maternal education and environment. In addition, self acceptance concept also influenced by passage of time associated with the trauma healing process and memories recollecting of their parents death or life divorce. Those factors above will also influence their future achievement.